2017
DOI: 10.1097/bot.0000000000000875
|View full text |Cite
|
Sign up to set email alerts
|

Time From Injury to Surgical Fixation of Diaphyseal Humerus Fractures Is Not Associated With an Increased Risk of Iatrogenic Radial Nerve Palsy

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
1
4
0
2
Order By: Relevance
“…e difficulty in an anatomical reduction in the delayed group may explain our result of a higher delayed union rate. Meanwhile, the incidence of iatrogenic radial nerve injuries did not differ significantly between the early and delayed groups in this study; this is analogous to a previously reported finding that delayed intervention for humeral shaft fractures did not increase the risk for radial nerve palsy [4]. e rate of postoperative infection in this study was 2.3%, which was similar to the rate of 3-5% reported in previous studies [10,11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…e difficulty in an anatomical reduction in the delayed group may explain our result of a higher delayed union rate. Meanwhile, the incidence of iatrogenic radial nerve injuries did not differ significantly between the early and delayed groups in this study; this is analogous to a previously reported finding that delayed intervention for humeral shaft fractures did not increase the risk for radial nerve palsy [4]. e rate of postoperative infection in this study was 2.3%, which was similar to the rate of 3-5% reported in previous studies [10,11].…”
Section: Discussionsupporting
confidence: 90%
“…Surgical treatment of humeral shaft fractures has been reported to yield relatively satisfactory results compared to conservative treatment; however, there are complications, such as delayed bone union, nonunion, iatrogenic radial nerve injury, and infection [1][2][3]. To date, little has been reported on the factors affecting postoperative complications of humeral shaft fractures [3,4]. Furthermore, the effects of the timing of surgery on the clinical outcomes for acute humeral shaft fractures remain unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the patient during general anesthesia is also a causative factor as loss of muscle tone can lead to inadvertent traction at the fracture site and compression of the radial nerve [ 13 ]. For the most part, radial nerve entrapment is seen after fracture manipulation when the nerve is unknowingly entrapped between bone and an installed plate, compressed by a bone fragment or if excessive nailing of the bone occurs [ 14 ]. A study concluded that in 78% of patients suffering from iatrogenic radial nerve palsy, the injury occurred after a plate osteosynthesis approach.…”
Section: Reviewmentioning
confidence: 99%
“…Ятрогенные повреждения лучевого нерва при хирургическом лечении диафизарных переломов плечевой кости возникают, по разным данным, в 8-19% случаев [1][2][3]. Такие повреждения часто (до 46% случаев) сопровождаются продолжительными, до 9-14 месяцев, двигательными и чувствительными расстройствами [4].…”
Section: Introductionunclassified
“…Терапевтическое лечение нейропатии после выполненной ревизии лучевого нерва не обсуждается в зарубежных профильных публикациях [3,8,12], а в работах отечественных авторов отсутствует единство взглядов на такое лечение [4,5,11,[22][23][24].…”
Section: Introductionunclassified